Talent Management in Academics: Nurturing the Knowledge Pool - Lavania, Dolly (Prabandhan: Indian Journal of Management, 2010)
"Talent" connotes different meaning to different people. It has different meaning in different contexts also. The meaning of talent is different for someone serving a corporate than someone serving defence services, serving civil services etc. Therefore, it is germane to first decide in what context one is talking about then the meaning of talent. In this paper, the word ’talent’ is used in the context of "ACADEMICS" and for Academic Institutions. Talent is like the person who climbed the Himalayas to the guru’s cave to ask "what is the meaning of life?" and got the answer "Oh I was hoping you might be able to tell me dear sonâ€¦" So, there is no one answer to this question. Just to cite an example from the Gita, which says that there is no plant that grows on the surface of the earth which does not have medicinal value; there is no sound in the universe that cannot form a mantra and that there is no man born who does not have a talent, only one has to have an eye to recognize the hidden talent in himself. The use of the word "talent" has become almost jaded but not quite in the category of academics which is extremely serious and sincere in its true sense because it is not only concerned with the society and country at large but with the entire human civilization. One of the major issues for higher education is ensuring the continued excellence of its faculty, to continuously improve and compete in the future and as the number and diversity of students is increasing, creating an institutional environment that values the recruitment and retention of an excellent and diverse faculty is more important than ever.